Assessment of generalisability in trials of health interventions: suggested framework and systematic review. Issue 7563 (10th August 2006) - Bonell, C; Oakley, A; Hargreaves, J; Strange, V; Rees, R
Abstract : Most evaluations of new treatments use highly selected populations, making it difficult to decide whether they would work elsewhere. Systematic evaluation and reporting of applicability is required